2023
DOI: 10.3390/membranes13060562
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of Seawater Reverse Osmosis Brine by Monovalent Ion-Selective Membranes through Electrodialysis

Abstract: This paper proposes the use of monovalent selective electrodialysis technology to concentrate the valuable sodium chloride (NaCl) component present in seawater reverse osmosis (SWRO) brine for direct utilization in the chlor-alkali industry. To enhance monovalent selectivity, a polyamide selective layer was fabricated on commercial ion exchange membranes (IEMs) through interfacial polymerization (IP) of piperazine (PIP) and 1,3,5-Benzenetricarbonyl chloride (TMC). The IP-modified IEMs were characterized using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Sharma et al enhanced the monovalent selectivity by fabricating a polyamide selective layer on commercial IEMs through interfacial polymerization (IP), which was then utilized for concentrating NaCl in seawater reverse osmosis brine. The results demonstrated that the IP-modified IEMs exhibited a divalent rejection rate exceeding 90%, whereas the commercial IEMs displayed a divalent rejection rate below 65% [36].…”
Section: Introductionmentioning
confidence: 97%
“…Sharma et al enhanced the monovalent selectivity by fabricating a polyamide selective layer on commercial IEMs through interfacial polymerization (IP), which was then utilized for concentrating NaCl in seawater reverse osmosis brine. The results demonstrated that the IP-modified IEMs exhibited a divalent rejection rate exceeding 90%, whereas the commercial IEMs displayed a divalent rejection rate below 65% [36].…”
Section: Introductionmentioning
confidence: 97%